Hubungan Antara Pola Asuh Permisif Dengan Kepercayaan Diri Remaja - Yusuf, Ridho Novriansyah; Sudarman, Sudarman; Fitriani, Annisa; Syafrimen, Syafrimen (ANFUSINA: Journal of Psychology, 2020)
Confidence is a condition about a person's beliefs that look at him positively and can reach something he wants without any doubt. This study aims to determine the relationship between permissive parenting with adolescent self confidence in SMP Negeri 35 Bandar Lampung. The hypothesis proposed in this study is that there is a relationship between permissive parenting with adolescent self confidence in SMP Negeri 35 Bandar Lampung. The subjects of this study were adolescents of class VIII at SMP Negeri 35 Bandar Lampung in the academic year 2019/2020, taken using a purposive sampling technique. This study uses a data collection method in the form of a psychological scale, namely a confidence scale of 31 items (α = 0.889) and a permissive parenting scale of 30 items (0.929). The collected data were analyzed using the product moment analysis technique from Karl Pearson assisted with SPSS 22.0 for windows. The results of data analysis showed that rxy = 0,600 with p = 0,000 (p <0.01). This shows that there is a very significant relationship between permissive parenting with adolescent self-confidence, so that the hypothesis is accepted. These results make an effective contribution of 0.360 or 36%. In other words, the permissive parenting variable contributed 36% effectiveness to the variable confidence.Keywords: Self Confidence, and Permissive Parenting